Character Visualization on Kumbakarna Wanda Macan Wayang Kulit Purwa Surakarta Style - Herliyana Rosalinda (Universitas Indraprasta PGRI, 2019)
This article discusses the visual analysis of one type of Wanda character Kumbakarna wayang kulit purwa Surakarta style. Kumbakarna is one of the younger siblings of Dasamuka (Rahwana) in the Ramayana story. His face and figure are the same as his brother's in the form of a giant (blind) but his soul and heart are contradictory, he has a knight's soul even though it is on the antagonist's side. These two opposites rarely occur in puppet characters. In general, the giant character has a ferocious nature, evil and not callous, but this does not apply to the character of Kumbakarna. This article tries to describe and analyze the Kumbakarna figure from the side of his wanda, looking for distinguishing elements in terms of the anatomical features of the Kumbakarna wanda that symbolize the good figure and knight behind the sinister physical features.